2006
DOI: 10.1155/2006/407609
|View full text |Cite|
|
Sign up to set email alerts
|

Hypercalcemia in Patients with Newly Diagnosed Tuberculosis in Abuja, Nigeria

Abstract: Hypercalcemia is not uncommon among Nigerian patients with newly diagnosed TB, but it is rarely symptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…[13] In the incidence studies mentioned above, it was found that patients with granulomatous disorders and hypercalcemia were from areas where there was increased calcium and Vitamin D consumption in their daily diet. [56789] Our patient, a daily laborer also was a gentleman who used to work in the sun, which could explain the elevated circulating activated Vitamin D causing severe hypercalcemia. Our patient also had renal failure at presentation which could be one of the presentations of hypercalcemia.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[13] In the incidence studies mentioned above, it was found that patients with granulomatous disorders and hypercalcemia were from areas where there was increased calcium and Vitamin D consumption in their daily diet. [56789] Our patient, a daily laborer also was a gentleman who used to work in the sun, which could explain the elevated circulating activated Vitamin D causing severe hypercalcemia. Our patient also had renal failure at presentation which could be one of the presentations of hypercalcemia.…”
mentioning
confidence: 98%
“…[34] The incidence of hypercalcemia in tuberculosis varies from 2% to 25% depending on the geographical area where the study was conducted and is depended on multiple other factors such as the intake of calcium, Vitamin D, and exposure to the sun. [56789] In a study carried out in Jabalpur Military Hospital, in 94 patients with active tuberculosis, only 5 had hypercalcemia. [10] Mechanism of hypercalcemia in tuberculosis is considered to be due to the extra-renal production of 1,25(OH) 2 D 3 by alveolar macrophages and T lymphocytes possibly CD8 T lymphocytes.…”
mentioning
confidence: 99%
“…The prevalence of hypercalcemia in patients with tuberculosis is quite variable between countries, varying from approximately 2.3% in some studies (3) to 14.7-50.6% in other studies (6)(7)(8)(9)(10)(11)(12)(13)(14) ( Table 2). This variation has been largely attributed to disparity in vitamin D and calcium intake, the degree of sunlight exposure as well as the criteria for the diagnosis for hypercalcemia (4).…”
Section: Discussionmentioning
confidence: 99%
“…A close relation between abnormal calcium metabolism and radiological extent of disease has been described in pulmonary TB patients [33,34]. Alterations in serum calcium, particularly cases of hypercalcemia, have been observed in adult TB patients [33-35]. Hypercalcemia in pediatric TB patients is an infrequently recognized and poorly understood phenomenon [36].…”
Section: Discussionmentioning
confidence: 99%